Follow fashion: Britain’s continuing influence on the death penalty in the Caribbean - Affonso, Timothy A. (The Palgrave handbook of Caribbean criminology, 2024)
This chapter will critically examine the development of the death penalty from a socio-legal perspective. The social dimension relates to the exploration of the historical basis for the death penalty phenomenon in the Commonwealth Caribbean and its link to British colonial rule. There is also a need to interrogate the jurisprudence in the Caribbean as directed by the Judicial Committee of the Privy Council (JCPC) and simultaneously built upon by the Caribbean Court of Justice (CCJ). There will then be a need to explore the underlying issues of independence, indigenous law and post-colonialism in the attitude adopted by the British Court to the practice of the mandatory death penalty in the region.